The effect of geometric shape and building orientation on minimizing solar insolation on high-rise buildings in hot humid climate - Chia, Sok Ling; Ahmad, Mohd. Hamdan; Ossen, Dilshan Remaz (Universiti Sains Malaysia, 2007)

(untitled)
High-rise buildings are experiencing overheating condition in hot humid climate. For a high-rise built form, vertical surfaces are the most critical to theimpact of solar radiation. This study examines the effect of geometric shapes on the total solar insolation received by high-rise buildings. Two generic buildingshapes (square and circular) have been studied with variations in width-to-length ratio (W/L ratio) and building orientation using the computer simulationprogram ECOTECT V5.2. The results revealed that the circular shape with W/L ratio 1:1 is the most optimum shape in minimising total solar insolation. The squareshape with W/L ratio 1:1 in a north-south orientation receives the lowest annual total solar insolation compared to other square shapes. This optimum shape(CC 1:1) receives the highest amount of solar insolation on the east-orientated wall, followed by the south-, west- and north-orientated walls respectively. Thisstudy guides designers on choosing optimum geometric shape and appropriate orientation for high-rise buildings.